2012
DOI: 10.1111/cogs.12015
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Time Course of Word‐Frequency Effects in Auditory Word Recognition With Event‐Related Potentials

Abstract: Although the word-frequency effect is one of the most established findings in spoken-word recognition, the precise processing locus of this effect is still a topic of debate. In this study, we used event-related potentials (ERPs) to track the time course of the word-frequency effect. In addition, the neighborhood density effect, which is known to reflect mechanisms involved in word identification, was also examined. The ERP data showed a clear frequency effect as early as 350 ms from word onset on the P350, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
45
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 46 publications
13
45
1
2
Order By: Relevance
“…The onset was chosen to allow Kalman filter predictions to stabilize, and to capture early evoked responses beginning with the N1/M100 auditory potential. The endpoint was chosen based on evidence from MEG, ERP and eyetracking results that show that sensitivity to manipulations of phonotactic frequency or neighborhood density for spoken words between 200 ms and 500 ms for visually presented (Pylkkänen et al, 2002; Stockall, Stringfellow, & Marantz, 2004) and auditorily presented words (Dufour et al, 2013; Hunter, 2013; MacGregor, Pulvermuller, van Casteren, & Shtyrov, 2012). We report all analyses related to the WORD and LOW ENTROPY NONWORD conditions here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The onset was chosen to allow Kalman filter predictions to stabilize, and to capture early evoked responses beginning with the N1/M100 auditory potential. The endpoint was chosen based on evidence from MEG, ERP and eyetracking results that show that sensitivity to manipulations of phonotactic frequency or neighborhood density for spoken words between 200 ms and 500 ms for visually presented (Pylkkänen et al, 2002; Stockall, Stringfellow, & Marantz, 2004) and auditorily presented words (Dufour et al, 2013; Hunter, 2013; MacGregor, Pulvermuller, van Casteren, & Shtyrov, 2012). We report all analyses related to the WORD and LOW ENTROPY NONWORD conditions here.…”
Section: Resultsmentioning
confidence: 99%
“…Dufour et al (2013) provide the strongest evidence that phonological neighborhood and density effects have different timecourses. They found that simultaneous manipulation of phonotactic frequency-density influenced the amplitude of both the PMN and the late N400 (550–650 ms).…”
Section: Phonotactic Frequency Effectsmentioning
confidence: 87%
See 1 more Smart Citation
“…() showed immediate use of lexical information on speech perception (the Ganong effect), and Mitterer and Reinisch () showed that retuned phoneme categories immediately bias perception. Similarly, it has long been known that word frequency affects lexical processing from the earliest moments of perception (Dahan, Magnuson, & Tanenhaus, ; Dufour, Brunellière, & Frauenfelder, ). Thus, the evidence for immediate integration is ubiquitous.…”
Section: Introductionmentioning
confidence: 98%
“…Word frequency is an example. In lmer, word frequency is used as a predictor; in DIANA the relative word frequency serves as a prior probability during the search ( [17]). The actual effect of word frequency on DIANA's RT depends also on the neighborhood density, which in turn depends on the composition of the lexicon.…”
Section: Simulationmentioning
confidence: 99%